2003
DOI: 10.1037/0278-7393.29.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive decision making and working memory.

Abstract: Decision making that favors short-term over long-term consequences of action, defined as impulsive or temporally myopic, may be related to individual differences in the executive functions of working memory (WM). In the first 2 experiments, participants made delay discounting (DD) judgments under different WM load conditions. In a 3rd experiment, participants high or low on standardized measures of imupulsiveness and dysexecutive function were asked to make DD judgments. A final experiment examined WM load eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
435
4
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(470 citation statements)
references
References 60 publications
28
435
4
3
Order By: Relevance
“…Taxing working memory reduces people's ability to keep their long-term goals in mind and has detrimental consequences for self-control ability (Hinson et al, 2003;Shiv & Fedorikhin, 1999;Ward & Mann, 2000). Conversely, taxing the response inhibition component of executive functioning increases response inhibition in unrelated domains, which has a positive effect on self-control ability.…”
Section: Implications For Executive Functioningmentioning
confidence: 99%
“…Taxing working memory reduces people's ability to keep their long-term goals in mind and has detrimental consequences for self-control ability (Hinson et al, 2003;Shiv & Fedorikhin, 1999;Ward & Mann, 2000). Conversely, taxing the response inhibition component of executive functioning increases response inhibition in unrelated domains, which has a positive effect on self-control ability.…”
Section: Implications For Executive Functioningmentioning
confidence: 99%
“…The mechanism of this relationship is unclear. Since working memory load is associated with faster temporal discounting (Hinson, Jameson & Whitney, 2003), the relationship in question may stem from the working memory's involvement in intelligence by maintaining an active mental image of the goal and integrating diverse information (Shamosh & Gray, 2008). An alternative explanation is offered in the meta-analysis by Shamosh & Gray (2008), which showed that taking into account non-verbal intelligence resulted in only a slight increase in the relationship between intelligence and temporal discounting.…”
Section: Introductionmentioning
confidence: 99%
“…Lower working memory capacity or reduced deliberation / reflection time when making decisions are associated with impulsive decisions (Finn et al, 2002). Studies show that lower working memory capacity in younger populations is associated with less advantageous, impulsive decision-making (Bechara & Martin, 2004;Finn et al, 2002;Hinson et al, 2003). Furthermore, MRI studies have shown that aging is highly correlated with shrinkage in prefrontal regions such as the lateral prefrontal cortex, the orbitofrontal cortex, and in prefrontal grey and white matter volumes (Raz et al, 2004(Raz et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%